Rating of perceived exertion in professional volleyball: a systematic review - Rebelo, A.; Pereira, J. R.; Martinho, D. V.; Valente-dos-Santos, J. (Journal of Human Kinetics, 2023)
The rating of perceived exertion (RPE) is a non-invasive, cost effective, and time efficient strategy to measure training loads. However, data can be collected without following specific procedures and across a range of methods (e.g., different RPE scales and/or different operational questions). Consequently, practitioners working in professional volleyball can use this information in various ways with different assessment standards between them. Therefore, the purpose of the current review was to systematically and critically evaluate the use of RPE-based methods in professional volleyball athletes. Electronic searches were conducted in four databases (PubMed, SPORTDiscus, Scopus, and Web of Science). The electronic search yielded 442 articles, from which 14 articles were included in the systematic review. All included studies used the BORG-CR10 scale to calculate the session RPE. The main findings indicate that, to minimize the effect of the last exercise of the session, the athlete should be presented with the RPE question 10 to 30 minutes after the session is finished. Additionally, in order to evaluate the intensity of the training session, the question should be "how hard/intense was your session?", avoiding questions without these adverbs or adjectives such as "how was your training session/workout?". Future studies should analyse the collection of the localized RPE responses in professional volleyball athletes and their relationships with objective markers such as the number of jumps and accelerations.